Antiviral, immunomodulatory, and anticoagulant effects of quercetin and its derivatives: Potential role in prevention and management of COVID-19 - Souparnika H. Manjunath; Rajesh K. Thimmulappa (Elsevier, 2022)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has caused a devastating health crisis worldwide. In this review, we have discussed that prophylactic phytochemical quercetin supplementation in the form of foods or nutraceuticals may help manage the COVID-19 pandemic. The following evidence supports our argument. First, nuclear factor erythroid-derived 2-like 2 (NRF2) agonists abrogate replication of SARS-CoV-2 in lung cells, and quercetin is a potent NRF2 agonist. Second, quercetin exerts antiviral activity against several zoonotic coronaviruses, including SARS-CoV-2, mainly by inhibiting the entry of virions into host cells. Third, inflammatory pathways activated by nuclear factor kappa B, inflammasome, and interleukin-6 signals elicit cytokine release syndrome that promotes acute respiratory distress syndrome in patients with COVID-19, and quercetin inhibits these pro-inflammatory signals. Fourth, patients with COVID-19 develop thrombosis, and quercetin mitigates coagulation abnormalities by inhibiting plasma protein disulfide isomerase. This review provides a strong rationale for testing quercetin for the management of COVID-19.